Using cardiovascular risk stratification to identify those at high risk may be cost effective compared to the government strategy of national screening for all adults aged 40–74. Issue 5 (19th July 2010) - Waugh, Norman
Abstract : Commentary on: Chamnan P Simmons RK Khaw KT . Estimating the population impact of screening strategies for identifying and treating people at high risk of cardiovascular disease: modelling study . BMJ 2010 ;340 :c1693 .